Vocational students’ perception and readiness in facing globalization, industry revolution 4.0 and society 5.0 - Ali, M (Journal of physics. Conference series, 2021)
Globalization is marked by the enactment of cooperation agreements between countries such as the ASEAN Economic Community (AEC), ASEAN Free Trade Area (AFTA), China-ASEAN Free Trade Area (CAFTA), World Trade Organization (WTO), and other agreements. Globalization has resulted in the opening of goods, capital, investment, and labor between countries in the world. Higher education has a strategic role in preparing professional human resources to compete with workers from world countries. This article examines and analyzes Indonesian students’ readiness to face globalization, the industrial revolution 4.0, and society 5.0. The questionnaire was distributed to students from six departments at the Yogyakarta State University’s Faculty of Engineering to investigate this. Student readiness indicators include competency readiness (knowledge, skills, and attitudes), personal Readiness (self-confidence and mental), communication readiness, teamwork readiness, and technological Readiness. The results showed students’ readiness in facing globalization, the industrial revolution 4.0, and society 5.0 were in the Good category with an average score of 2.86 (71.5%). In detail, it can be explained, student readiness in the competency aspect gets a score of 2.86 (71.5%), personal readiness with an average score of 2.65 (65.5%), communication readiness has a score of 2.6 (65%), readiness teamwork with a score of 3.18 (79.5) and technology readiness with a score of 3.04 (76%).